2008
DOI: 10.1111/j.1475-4932.2008.00508.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Housing Equity Withdrawal: Evidence from a Microeconomic Survey*

Abstract: The increase in housing equity withdrawal and coincident decline in aggregate savings rates in a number of countries in recent years is consistent with the consumption‐smoothing model of housing equity withdrawal. However, there are a variety of other theoretical models that purport to explain why households withdraw and inject equity. To assess the relative importance of these various theories, we use a comprehensive survey of the equity withdrawal and injection decisions of Australian households. We find sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 10 publications
2
12
1
Order By: Relevance
“…Households are more likely to withdraw home equity if they face a negative income shock, get divorced or married, or have higher home equity. In contrast to the finding by Schwartz et al (2008), younger households are more likely to withdraw, suggesting that for this data and definition of HEW, consumption smoothing considerations dominate among life-cycle effects.…”
Section: Theoretical Background and Empirical Evidencecontrasting
confidence: 85%
See 1 more Smart Citation
“…Households are more likely to withdraw home equity if they face a negative income shock, get divorced or married, or have higher home equity. In contrast to the finding by Schwartz et al (2008), younger households are more likely to withdraw, suggesting that for this data and definition of HEW, consumption smoothing considerations dominate among life-cycle effects.…”
Section: Theoretical Background and Empirical Evidencecontrasting
confidence: 85%
“…While these studies focus on gross HEW, i.e. before use of funds, through refinancing, Schwartz et al (2008) analyse net withdrawal or net injections, i.e. total injections into housing minus total amount withdrawn, in 2004 using a survey of Australian households.…”
Section: Theoretical Background and Empirical Evidencementioning
confidence: 99%
“…25 The probability of withdrawing equity increases until around the age of 55 and decreases afterwards. This confirms findings by Schwartz et al (2008) and is consistent with the view that households first have to build up housing equity in early years that can be used later on.…”
Section: Non-transactorssupporting
confidence: 80%
“…Banks 2009;Schwartz et al 2008;Hurst and Stafford 2004), when households withdraw home equity. This study adds evidence on continental Europe and tests the implications from theoretical models incorporating home equity withdrawal, using information from the Dutch National Bank Household Survey (DHS) for the period 2004 to 2007.…”
Section: Introductionmentioning
confidence: 99%
“…In Australia and the UK, it was found that households facing financial difficulties were more likely to take out an extra mortgage or extend their existing mortgage (Benito 2009;Parkinson and Searle 2009;Schwartz et al 2008). To date, there have been no indications that households in the Netherlands have been using mortgage-equity release in case of financial difficulties.…”
Section: Theorymentioning
confidence: 99%